Effects of pore structure on wide-frequency electromagnetic interference shielding performance of carbonized wood. (February 2023) - Dai, Zhenhua; Wei, Yuyi; Hu, Chuanshuang; Wang, Zhuoqun; Wei, Aizhen; Zhang, Weiwei; Lin, Xiuyi
Abstract: Carbonized wood attracts widespread attention in the field of electromagnetic interference (EMI) shielding thanks to its layered porous structure and high electrical conductivity. Understanding the correlation between pore structure and shielding performance is crucial for constructing efficient EMI shielding materials. Herein, pore structures are monitored by changing the compression ratio during the hot pressing. Carbonized wood with a 40% compression ratio displays a superior EMI shielding effectiveness (SE) up to 71.69 dB in K-band, owing to the optimal structure. EMI shielding characteristics of carbonized wood in different frequency ranges are also studied. The effects of pore structure on the shielding performance are further illuminated by finite element analysis. After structure optimization, carbonized wood can demonstrate high EMI shielding performance, wide-frequency coverage, terahertz band use, and excellent heat dissipation. This work inspires the design of next-generation sustainable EMI shielding materials. Graphical abstract: Image 1 Highlights: A tunable electromagnetic shielding property is achieved by changing the compression ratio of carbonized poplar wood. The absorption of incident electromagnetic waves by carbonized poplar wood increases with increasing frequency and decreasing pore size. Carbonized poplar wood shows better heat dissipation and satisfactory compressive strength at higher compression ratio. Carbonized poplar wood after 40% compression demonstrates excellent EMI shielding performance at wide frequency.